Hubungan Asupan Lemak Dan Asupan Serat Dengan Tekanan Darah Pada Pasien Hipertensi Usia 35-75 Tahun Di Wilayah Uptd Puskesmas Pasiran Jaya - Rima Septiana; Dera Elva Junita; Desti Ambar Wati; Mayesti Akhriani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Hypertension is a condition when systolic blood pressure is > 120 mmHg and diastolic blood pressure is > 80 mmHg. Factors that influence the occurrence of hypertension are such as diet (sodium, potassium, fiber, and fat intake), as well as exercise habits. Low fiber intake can cause less excretion of bile acids through feces, resulting in a lot of cholesterol being absorbed from the bile. Cholesterol that is widely distributed in the blood vessels will inhibit blood circulation, thus increasing blood pressure. The purpose of this study was the relationship between fat intake and fiber intake with blood pressure in hypertensive patients aged 35-75 years at the Pasiran Jaya Health Center UPTD in 2024. This study was conducted in September - November 2024. The design in this study used a quantitative design with the approach used was cross sectional, the sample of this study was hypertensive respondents in the Pasiran Jaya Health Center UPTD Area, Tulang Bawang Regency, as many as 103 respondents with the sampling technique used was accidental sampling. the measuring instrument used was the SQ FFQ instrument and blood pressure. The bivariate analysis of this study used the Pearson test. The results of the statistical test analysis showed that there was a relationship between fat intake and systolic blood pressure with a P Value (p = 0.027) and diastolic (p = 0.032) in hypertensive patients aged 35-75 years in the Pasiran Jaya Tulang Bawang Health Center UPTD Area in 2024. The results of the statistical test analysis There is a relationship between fiber intake and systolic blood pressure with a P Value (p = 0.003) and diastolic (p = 0.001) in hypertensive patients aged 35-75 years in the Pasiran Jaya Tulang Bawang Health Center UPTD Area in 2024. Every patient is expected to be able to consume sufficient fat and fiber so that blood pressure remains normal.